Thermo-Physical Properties of Dispersion Nuclear Fuel for a New-Generation Reactors: A Computational Approach; AIP Conference Proceedings; Vol. 2101 : Isotopes: Technologies, Materials and Application (ITMA-2018) - Bedenko S. V. Sergey Vladimirovich; Karengin A. G. Aleksander Grigorievich; Nima Ghal-Eh; Alekseev N. Nikita; Knyshev V. V. Vladimir Vladimirovich; Shamanin I. V. Igor Vladimirovich (2019, 2019)
Title screen